2019
DOI: 10.1186/s13578-019-0328-5
|View full text |Cite
|
Sign up to set email alerts
|

Steroid receptor coactivator 3 inhibits hepatitis B virus gene expression through activating Akt signaling to prevent HNF4α nuclear translocation

Abstract: Background Chronic hepatitis B virus (HBV) infection is one of the most serious global public health problems. The role of steroid receptor coactivator 3 (SRC-3) in HBV biosynthesis is unknown. The aim of this study is to investigate the function of SRC-3 in regulating HBV biosynthesis both in vitro and in vivo and to identify the underlying mechanism. Results In this study, we found that knockdown of SRC-3 could increase the levels of HBV mRNA and HBV proteins HBsAg an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The PI3K/AKT signaling pathway plays an important role in regulating the transcriptional activities of SP1 and HNF4α ( Adapala et al, 2019 ; Gómez-Villafuertes et al, 2015 ; Li et al, 2019 ; Zhao et al, 2015 ). Activation of AKT promotes the stability and localization of SP1 by phosphorylating SP1 at Thr453 and Thr739 ( Adapala et al, 2019 ; Gómez-Villafuertes et al, 2015 ; Zhao et al, 2015 ), and prevents the nuclear translocation of HNF4α ( Li et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The PI3K/AKT signaling pathway plays an important role in regulating the transcriptional activities of SP1 and HNF4α ( Adapala et al, 2019 ; Gómez-Villafuertes et al, 2015 ; Li et al, 2019 ; Zhao et al, 2015 ). Activation of AKT promotes the stability and localization of SP1 by phosphorylating SP1 at Thr453 and Thr739 ( Adapala et al, 2019 ; Gómez-Villafuertes et al, 2015 ; Zhao et al, 2015 ), and prevents the nuclear translocation of HNF4α ( Li et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The PI3K/AKT signaling pathway plays an important role in regulating the transcriptional activity of Sp1 and HNF4α (Adapala et al, 2019, Gomez-Villafuertes et al, 2015, Zhao et al, 2015, Li et al, 2019). Activation of AKT promotes the stability and localization of Sp1 by phosphorylating Sp1 at threonine sites 453 and 739 (Adapala et al, 2019, Gomez-Villafuertes et al, 2015, Zhao et al, 2015), and prevents the nuclear translocation of HNF4α (Li et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The PI3K/AKT signaling pathway plays an important role in regulating the transcriptional activity of Sp1 and HNF4α (Adapala et al, 2019, Gomez-Villafuertes et al, 2015, Zhao et al, 2015, Li et al, 2019). Activation of AKT promotes the stability and localization of Sp1 by phosphorylating Sp1 at threonine sites 453 and 739 (Adapala et al, 2019, Gomez-Villafuertes et al, 2015, Zhao et al, 2015), and prevents the nuclear translocation of HNF4α (Li et al, 2019). Consistent with these observations, we found that suppression of AKT by siRNA or its inhibitors significantly inhibited the accumulation of phospho-Sp1 in the nucleus, but remarkably promoted nuclear translocation of HNF4α (Figure 5H-5K).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the interactions between CRY and glucocorticoid receptors affect carbohydrate metabolism, hence transacting PER2 [ 87 ]. HNF4α increases the transcription of pgRNA in hepatoma cells and thus affects HBV biosynthesis[ 88 ]. In addition, P2-HNF4α inhibits the expression of BMAL1 , leading to the localization of P1-HNF4α from the nucleus to the cytoplasm.…”
Section: Circadian Rhythmmentioning
confidence: 99%